Islamic Integrated-Based School Principal Decision Making In Junior High School - Devi Yana, Vinda; Asmendri, Asmendri (Journal of Islamic Education Students (JIES), 2021)
School principal decision-making is essentially a change in certain conditions. The purpose of this study was to describe the process of Islamic integrated-based decision-making by the junior high school principals. Descriptive qualitative was chosen as the method of the research. Sources of data in this study were principal, vice-principal, head of administration, and teachers at SMP IT Qurrata AÔÇÖyun Batusangkar. The data were collected using observation, interview, and documentation techniques. The result of the study described that making decisions in an education organization could run well by doing the right procedures of analyzing problems, developing solution alternatives, making decisions after discussion, implementing the decision, and evaluating. The principalÔÇÖs decision-making is a determinant of strategic policies in realizing programs at his/her school.┬á ┬á┬á┬á